Reliability of novice physiotherapists for measuring Cobb angle using a digital method - Patcharawan Suwannarat, PT, PhD; Pattra Wattanapan, MD; Arpassanan Wiyanad, PT, MSc; Pakwipa Chokphukiao, PT, MSc; Sininat Wilaichit, PT, MPH; Sugalya Amatachaya, PT, PhD (World Scientific Publishing, 2017)
Background: The Cobbâs method is the most accurate and reliable method for kyphosis measurement. Conventionally, a sagittal Cobb angle was commonly derived from a lateral plain film. With computer technology, a digital method is widely used in common clinical settings, but the existing reliability data involved only experienced raters. Objectives: To assess the interrater and intrarater reliability of a digital Cobbâs method using novice physiotherapists. Methods: Fifteen participants, with an occiput wall distance of more than 0Â cm, were interviewed and assessed for their demographics. Then they were filmed for lateral spinal radiography over the area of thoracic spine in a standing position, and the Cobb angle was analyzed by four raters, including an expert physician and three novice physiotherapists, using a SurgimapSpine programme. Results: The average Cobb angles among the four raters showed no significant difference (p=0.984). Outcomes of their measurements had excellent intrarater and interrater reliability [intraclass correlation coefficient (ICC3,3)=0.995â0.997] with a small range of standard errors of the measurement (<1Â°). Conclusion: A digital Cobbâs method had excellent reliability when used by a novice health professional rater. The findings confirm the ease of using this method to detect and monitor kyphosis in general hospitals, clinics, or research facilities. Keywords: Cobb angle, spinal angle, reliability, spinal deformity, X-ray